The Brazilian Economy Today Towards a New Socio-Economic Model? - Pereira, Anthony W.; Pereira, Anthony W.; Mattei, Lauro.; Mattei, Lauro. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Pereira and Mattei bring contributors together in this exciting volume to further understanding about the recent Brazilian Economic Development Model and discuss the related social conditions. The authors analyze both the political economy and social public policies to highlight new opportunities to create a sustainable development model.